2016
DOI: 10.5665/sleep.5632
|View full text |Cite
|
Sign up to set email alerts
|

Regional Patterns of Elevated Alpha and High-Frequency Electroencephalographic Activity during Nonrapid Eye Movement Sleep in Chronic Insomnia: A Pilot Study

Abstract: These results suggest that even during the deepest stage of sleep, sensory and sensorimotor areas in insomnia subjects may still be relatively active compared to control subjects and to the rest of the sleeping brain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
79
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(83 citation statements)
references
References 77 publications
(89 reference statements)
4
79
0
Order By: Relevance
“…Source localization analysis found those differences likely originated from the frontal gyri and the anterior cingulate [46]. A recent high-density EEG pilot study found that individuals with PI had greater alpha and theta levels during N3 (delta) sleep than GS, suggesting that “wake-like” brain activity persists in insomnia even during the deepest stages of sleep [47]. Source localization suggested the heighted brain activity during NREM sleep originates from sensory and sensorimotor cortical areas [47].…”
Section: Functional Neuroimaging Studies Of Insomniamentioning
confidence: 99%
See 1 more Smart Citation
“…Source localization analysis found those differences likely originated from the frontal gyri and the anterior cingulate [46]. A recent high-density EEG pilot study found that individuals with PI had greater alpha and theta levels during N3 (delta) sleep than GS, suggesting that “wake-like” brain activity persists in insomnia even during the deepest stages of sleep [47]. Source localization suggested the heighted brain activity during NREM sleep originates from sensory and sensorimotor cortical areas [47].…”
Section: Functional Neuroimaging Studies Of Insomniamentioning
confidence: 99%
“…A recent high-density EEG pilot study found that individuals with PI had greater alpha and theta levels during N3 (delta) sleep than GS, suggesting that “wake-like” brain activity persists in insomnia even during the deepest stages of sleep [47]. Source localization suggested the heighted brain activity during NREM sleep originates from sensory and sensorimotor cortical areas [47]. As noted in the previous section, increased high-frequency EEG activity during wakefulness and “wake-like” EEG activity during NREM sleep may be due to reduced inhibition as well as increased excitation in particular brain regions.…”
Section: Functional Neuroimaging Studies Of Insomniamentioning
confidence: 99%
“…Although it may be seen in asymptomatic subjects (Scheuler et al 1983;Horne and Shackell 1991), its prevalence and extent are clearly greater in these disorders such that a clinical association is well established. Whether alpha intrusion causes the patient's complaints, is a consequence of disruptive stimuli, or both is not clear (Riedner et al 2016;Pivik and Harman 1995;Stone et al 2008). Large studies are needed to identify its clinical significance.…”
Section: Assessment Of Alpha Intrusion (Alpha-delta Sleep)mentioning
confidence: 99%
“…Intrusion of alpha activity in non-REM sleep is frequently present in patients with fibromyalgia, chronic fatigue and non-restorative sleep (Anch et al 1991;Branco et al 1994;Moldofsky et al 1975;Olsen et al 2013), arthritis (Mahowald et al 1989), insomnia (Martinez et al 2010;Riedner et al 2016) and depression (Hauri and Hawkins 1973;Jaimchariyatam et al 2011). Although it may be seen in asymptomatic subjects (Scheuler et al 1983;Horne and Shackell 1991), its prevalence and extent are clearly greater in these disorders such that a clinical association is well established.…”
Section: Assessment Of Alpha Intrusion (Alpha-delta Sleep)mentioning
confidence: 99%
“…Basic scientific work over the past decades indicates that insomnia is characterized by persistent (24 h) hyperarousal as a final common pathway [38,39], as indicated, for instance, by decreased slow-wave sleep, increased fast-frequency (EEG β range) power during NREM sleep [40], and increased indices of local wakefulness during sleep [41]. However, these studies show a substantial variance across patients with insomnia and it appears to be important to further characterize individual alterations of sleep.…”
Section: Insomniamentioning
confidence: 99%